AB INITIO INVESTIGATION OF 12-CROWN-4 AND BENZO-12-CROWN-4 COMPLEXES WITH Li+, Na+, K+, Zn2+, Cd2+, AND Hg2+ - Yahmin Yahmin; Harno Dwi Pranowo; Ria Armunanto (Universitas Gadjah Mada, 2010)
The structure and binding energies of 12-crown-4 and benzo-12-crown-4 complexes with Li+, Na+, K+, Zn2+, Cd2+, and Hg2+were investigated with ab initio calculations using Hartree-Fock approximation and second-order perturbation theory. The basis set used in this study is lanl2mb. The structure optimization of cation-crown ether complexes was evaluated at HF/lanl2mb level of theory and interaction energy of the corresponding complexes was calculated at MP2/lanl2mb level of theory (MP2/lanl2mb//HF/lanl2mb). Interactions of the crown ethers and the cations were discussed in term of the structure parameter of crown ether. The binding energies of the complexes show that all complex formed from transition metal cations is more stable than the complexes formed from alkali metal cations.